Kesadaran Fertilitas pada Penyedia Layanan Kesehatan di Puskesmas Tambora, Jakarta Barat - Andriana Kumala Dewi; Cindy Yusliani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Objective: To determine the level of awareness of health workers towards fertility at Tambora Health Center, especially regarding age-related fertility decline. Methods: A survey was conducted on health workers at Tambora Health Center, West Jakarta on May 18, 2024. Participants were given a questionnaire regarding their perceptions and knowledge of fertility issues consisting of seven questions. The instrument has shown good validity, reliability, and consistency with Cronbach's alpha > 0.7. Descriptive analysis was used to describe the data using SPSS. Results: The majority of respondents believed that the most fertile age is 26-28 years (53%). Most respondents believed that there is a slight decline in a woman's ability to conceive at the age of 36-45 years (75%). Twenty-five percent of respondents stated that the chances of success for infertile couples undergoing IVF are 40-100%. Conclusion: Despite rapid progress in the development of fertility in clinical practice, this study shows that awareness of fertility is still low among health workers. There is a need for increased education for health care providers regarding fertility knowledge.